CONCEPTUALIZING PESANTREN SYSTEM IN ORGANIZATIONAL PERSPECTIVE - Perawironegoro, Djamaluddin (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
There have been many researchers studied about Pesantren by Islamic management education approach. A much-studied focus on the factors that contribute to the dynamic of Pesantren life, such as; leadership by Kyai, organizational culture, Pesantren strategy, change management, human resource management, organizational structure, and learning strategy. The study was conducted partially if there were at most two factors between the various factors. However, there is still very little scholars look the driving force for Pesantren system with the comprehensive point. Furthermore, this partial understanding has implications for partial development than the expected development is not optimal. This article will present a concept of Pesantren system in an organizational perspective. For that matter, this article will describe the concept of organizational system and the system in Pesantren, which then elaborated. Ultimately, there are several suggestions for mobilizing Pesantren through a system approach, in the hope that the purpose of Pesantren can be achieved effectively and efficiently. Pesantren system with the comprehensive point. Furthermore, this partial understanding has implications for partial development than the expected development is not optimal. Pesantren strategy, change management, human resource management, organizational structure, and learning strategy.